Temperature modeling and emulation of an ASIC temperature monitor system for Tightly-Coupled Processor Arrays (TCPAs) - E. Glocker; S. Boppu; Q. Chen; U. Schlichtmann; J. Teich; D. Schmitt-Landsiedel (Advances in Radio Science, 2014)
This contribution provides an approach for emulating the behaviour of an ASIC temperature monitoring system (TMon) during run-time for a tightly-coupled processor array (TCPA) of a heterogeneous invasive multi-tile architecture to be used for FPGA prototyping. It is based on a thermal RC modeling approach. Also different usage scenarios of TCPA are analyzed and compared.